Medical Encounters and Exchange in Early Canadian Missions - Parsons, Chris (Scientia Canadensis, 2008)
AbstractThe exchange of medical and pharmaceutical knowledge was an important facet of the encounter between native and newcomer in early Canada. Throughout New France Récollet and Jesuit missionaries were given privileged access both to indigenous peoples and indigenous plants. Curiously, however, when it came to describing medical treatments, it was people, rather than medicinal plants, that were targets of what might be called “the descriptive enterprise.” Attempting to divide suspect shamanic remedies from those deemed natural, missionary observers carefully documented the context of medical treatments rather than simply the specific remedy applied for treatment. Using records left by early Canadian missionaries this paper will look at the peculiar character of medical exchange in the missions of seventeenth and eighteenth-century New France to look at the interpersonal encounters that formed a constitutive element of colonial botany and framed the way in which indigenous knowledge was represented to metropolitan audiences.